An Occult Lacrimal Sac Diverticula Incidentally Found on Exploration after Tectonic Penetrating Keratoplasty for a Leaky Cicatrix in a Patient with Marfan Syndrome - Niveditha Narayanan; Sonam Poonam Nissar; Nimisha Nagpal (Delhi Journal of Ophthalmology)
We report a lacrimal sac diverticulum found incidentally on exploration after a tectonic penetrating keratoplasty performed for an anterior staphyloma with a leaky cicatrix. It was done in the left eye (LE) of a Marfan’s syndrome patient with bilateral congenital subluxated lenses who developed corneal decompensation after he underwent cataract surgery elsewhere with anterior chamber intraocular lenses 13 years ago. The fibrillin-1 gene mutation in Marfan’s syndrome could have predisposed to the diverticulum formation in the LE and corneal perforation in that eye highlights the importance of a protective healthy ocular environment.